A randomized controlled trial of Shengji ointment combined with bromelain in promoting healing of tendon-exposed diabetic foot wounds: integrated 16S rDNA sequencing and metabolomics analysis - Sun, Xu; Song, Jielin; Sun, Junchao; Zhang, Zhaohui (Frontiers in Pharmacology, 2025)
BackgroundDiabetic foot tendon exposures are prone to infection, necrosis, and prolonged treatment cycle, not only hinder wound healing, but may also lead to amputation and even life-threatening. Utilizing Shengji ointment (a Traditional Chinese Medicine, TCM) combined with bromelain for treating diabetic foot tendon exposure wounds has demonstrated preliminary efficacy. However, the underlying mechanisms, as well as the changes in wound microbiota and metabolites before and after treatment, still warrant further investigation.MethodsThis study used a randomized controlled trial design, with 60 patients randomly assigned to either the experimental group or the control group in a 1:1 ratio. The treatment cycle was 4 weeks. The experimental group was treated with Shengji ointment combined with bromelain, while the control group was treated with hydrocolloid dressing. The clinical efficacy of the two groups was evaluated through a controlled study, while wound exudates were collected only from the experimental group before and after treatment for 16S rDNA sequencing and metabolomics analysis to evaluate changes in wound microbiota and metabolites.ResultsFollowing the treatment, the granulation tissue coverage, wound healing rate, and Maryland Foot Function Score in the experimental group were markedly superior to those of the control group. Post-treatment analysis revealed significant changes in the wound microbiota composition of the trial group, with a reduction in potential pathogenic bacteria, including Erysipelatoclostridium, Lachnoclostridium, Pontimonas, Hydrogenovibrio, and Aquabacterium, alongside an increase in beneficial bacteria, such as Cetobacterium and Allisonella. Furthermore, 4,034 differential metabolites were identified, with 1907 upregulated and 2,127 downregulated, involving key metabolic pathways such as phenylpropanoid biosynthesis, tyrosine metabolism, and amino acid biosynthesis. Correlation analysis indicated a strong negative association between Pontimonas, Hydrogenovibrio, Aquabacterium, and the majority of the differential metabolites.ConclusionThe Shengji ointment combined with bromelain has shown notable effectiveness in treating diabetic foot wounds with tendon exposure by modulating microbial composition (reducing pathogenic bacteria and increasing beneficial bacteria) and optimizing the metabolic environment (targeting key metabolic pathways), providing valuable insights for further exploration of its mechanisms.